Efficient total synthesis of neocryptolepine and synthetic access to 6-methylquinindoline from a common intermediate - Kaufman, Teodoro Saúl (2017)
Fil: Fil: Kaufman, Teodoro Saúl. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Química Rosario. CONICET; Argentina